PENGARUH PERTUMBUHAN PENDUDUK, TINGKAT PENDIDIKAN, DAN UPAH MINIMUM KABUPATEN/KOTA (UMK) TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI BALI - Banyuning, I Gusti Agung Gede Bayu; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 4 (2022): Vol. 11 No. 4, April 2022 [1215-1619]DO - 10.24843/EEP.2022.v11.i04.p09, 2022)
The economic growth of the Province of Bali shows a fluctuating disparity between regencies/cities, and even tends to slow down every year. The purpose of this study is to analyze the effect of population growth, education level, and district/city minimum wages simultaneously and partially on the economic growth of districts/cities in Bali Province and the dominant variables affecting district/city economic growth in Bali Province. The data used is secondary data in 9 districts/cities in Bali Province in the period from 2015 to 2019 (5 years), so the number of observations is 45. The analytical technique used is multiple linear regression analysis. The results showed that population growth, education level and the district/city minimum wage simultaneously had a significant effect on economic growth. Population growth partially has a negative and significant effect, while the level of education and minimum wages partially has a positive and significant effect on economic growth. The district/city minimum wage is the variable has dominant influence on the economic growth of districts/cities in Bali Province. It is hoped that the government will more evenly distribute development between regions through the construction of new growth centers in all regions in accordance with the potential of each region, in addition to paying attention to the education budget so that it tends to increase according to applicable regulations, namely at least 20 percent of the APBD, and companies must be more committed in implementing wages so that workers can maximize their work. Keywords : Population Growth, Education, Minimum Wage, Economic Growth